Molecular Signaling Pathways Involved in the Glucose-Lowering Effect of Teucrium polium - Mannan, Adnan (Curtin University, 2017)
This thesis demonstrates that an extract of Teucrium polium, a Mediterranean herb with folklore reputation for the treatment of diabetes, does indeed have antidiabetic properties. It promotes insulin secretion from pancreactic beta cells and also has some insulin-like properties. For example, it promotes glucose uptake and storage as glycogen in muscle cells. The plant extract might be an impactful target for future drug discovery efforts for the treatment of type 2 diabetes and related disorders.